17β-Estradiol Regulates Glucose Metabolism and Insulin Secretion in Rat Islet β Cells Through GPER and Akt/mTOR/GLUT2 Pathway - Bian, Che; Bai, Bowen; Gao, Qian; Li, Siyi; Zhao, Yuyan (Frontiers in Endocrinology, 2019)
Aims: To explore the molecular mechanism by which 17β-estradiol (estrogen 2, E2) regulates glucose transporter 2 (GLUT2) and insulin secretion in islet β cells through G protein-coupled estrogen receptor (GPER) via Akt/mTOR pathway. Methods: SPF-grade SD male rats were used to establish an in vivo type 2 diabetes model treated with E2. Rat insulinoma cells (INS-1) were cultured in normal or high glucose media with or without E2. Immunofluorescence double staining was used to detect GPER, GLUT2, insulin and glucagon immunolocalization in rat islet tissues. Western blot was used to detect GPER, Akt, mTOR and GLUT2 protein immunocontent. Real-time PCR detected Slc2a2 and glucose kinase (GK) content, and ELISA was used to detect insulin levels. Glucose uptake, GK activity and pyruvate dehydrogenase (PDH) activity were analyzed with glucose detection, GK activity and PDH activity assay kit. Results: Immunofluorescence double staining confocal indicated that E2 treatment up-regulated expression levels of GPER, GLUT2 and insulin, while down-regulated glucagon. Western blot results revealed E2 increased GPER, Akt/mTOR pathway, and GLUT2 protein immunocontent. Real-time PCR showed E2 elevated Slc2a2, GK content. Moreover, E2 improved insulin secretion, glucose uptake, GK activity, and PDH activity. Conclusion: Our findings indicated that exogenous E2 up-regulated GPER via the Akt/mTOR pathway to increase GLUT2 protein content and insulin secretion in islet β cells.